2012
DOI: 10.1212/wnl.0b013e318245d23c
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of brain tissue loss associated with freezing of gait in Parkinson disease

Abstract: GM frontal and parietal atrophy occur in PD-FOG patients. FOG in PD seems to share with executive dysfunction and perception deficits a common pattern of structural damage to the frontal and parietal cortices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
73
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 39 publications
13
73
4
2
Order By: Relevance
“…The present findings disagree with Goldman et al (2014), who found reduced GM volume in bilateral precentral gyrus (Goldman et al, 2014), and with other studies that found reduced GM in left precentral gyrus (Kostic et al, 2012;GonzalezRedondo et al, 2014). The precentral gyrus is the origin of the pyramidal tract; therefore, Shao et al (2014) suggested that the impairment of the precentral gyrus may partially contribute to the motor deficits of PD.…”
Section: Grey Matter Volume Of Motor Cortexcontrasting
confidence: 99%
“…The present findings disagree with Goldman et al (2014), who found reduced GM volume in bilateral precentral gyrus (Goldman et al, 2014), and with other studies that found reduced GM in left precentral gyrus (Kostic et al, 2012;GonzalezRedondo et al, 2014). The precentral gyrus is the origin of the pyramidal tract; therefore, Shao et al (2014) suggested that the impairment of the precentral gyrus may partially contribute to the motor deficits of PD.…”
Section: Grey Matter Volume Of Motor Cortexcontrasting
confidence: 99%
“…In this study, we used the FreeSurfer implementation of surfacebased analysis and our results demonstrate that patients with FOG exhibited atrophy of the bilateral cingulate cortex (mostly in mid-anterior part), left supplementary motor area (SMA), and right frontal operculum. In summary, earlier publications reported rather complex pattern of functional and morphological changes [6][7][8][9][10][11]29 , suggesting a complex pathophysiological substrate of FOG. Whereas the automatic control of gait appears to be subserved by brainstem nuclei and their corresponding circuits, involvement of cortical brain structures is presumed in FOG because of frequent manifestation of freezing in situations with emotional or cognitive context.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, when Tessitore et al 6 directly contrasted PD patients with and without FOG, they found GM atrophy in the left cuneus, lingual gyrus, precuneus, and posterior cingulate cortex. On the other hand, when comparing GM atrophy in PD patients with FOG to both control subjects and PD patients with no FOG, Kostic et al 7 observed atrophy of the left inferior frontal gyrus, left precentral gyrus, and left inferior parietal gyrus. Lastly, Herman et al 29 reported that FOG severity correlated with atrophy in the bilateral inferior parietal lobule, right angular gyrus, and bilateral caudate nuclei, although no significant group-wise differences were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown distributed brain atrophy in cortical and subcortical regions, including the frontal lobe, temporal lobe, parietal lobe, occipital lobe, and the limbic/paralimbic areas. [1][2][3][4][5][6][7][8] On the other hand, 1 study reported an increase of GM in the thalamus in patients with PD with unilateral resting tremor compared with controls. 9 A recent study has observed not only brain volume loss in the occipital region but also volume increase in the limbic/paralimbic system.…”
mentioning
confidence: 96%